Florida child care center directors' intention to implement oral health promotion practices in licensed child care centers. Issue 1 (December 2016) - Joshi, Ajay; Ocanto, Romer; Jacobs, Robin; Bhoopathi, Vinodh
Abstract Background To determine the factors associated with child care center directors' (CCCDs) intention to implement oral health promotion practices (OHPPs) in licensed childcare centers (CCCs) within the next year, and their self-perceived barriers in successfully implementing those practices. Methods For this cross-sectional study, a pretested 45-item online survey was sent to 5142 CCCDs assessing pediatric oral health knowledge, attitudes towards oral health, intention to implement OHPPs, and self-perceived barriers to implementing OHPPs. An adjusted logistic regression model determined the factors associated with CCCDs intention to implement OHPPs within the next year. Results Participants were 877 CCCDs, with mean age of 48.5 ± 10.5 years, of whom 96 % were women, and 74 % were whites (Response rate = 19.4 %). The majority (67 %) of respondents reported that they intended to implement OHPPs in their center within a year. Insufficient funding, lack of enough training in oral health, and limited time to promote oral health were the most frequently cited barriers to implementing OHPPs. CCCDs of non-White race (p = 0.02), with a college degree or above (p = 0.05), and with positive attitudes (p < 0.0001), were more likely to report that they will implement OHPPs within the next year compared to their counterparts. Conclusions CCCDs reported fewer barriers to implementing OHPPs within the next year, indicating that CCCs can be a suitable setting to promote oral health. CCCDs race, educational status and attitudes towards oral health strongly predicted their intention to implement OHPPs. Though this study assessed the intention of CCCDs to implement OHPPs in CCCs, it did not access the actual implementation of OHPPs by them. Therefore future research could longitudinally assess predictors for true implementation of OHPPs. In addition, researchers should adopt a more comprehensive, multi-level approach to assess the actual dental health needs of children attending these centers, along with parental, staff and center level characteristics, and other relevant factors related to implementing OHPPs.